2006
DOI: 10.1179/174329306x77047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluxes containing oxides on tungsten inert gas welding process

Abstract: The use of an inorganic powder, termed activating flux, is a technique that can be used to improve the tungsten inert gas welding process. The activated tunsten inert gas (ATIG) process greatly increases single pass depth penetration. In the present work the activating effect of different oxides on 304L stainless steel was studied, to determine the main relationships between the oxide propertie(s) and the weld bead geometry variation and consequently to determine the mechanism(s) occurring during the ATIG weld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 8 publications
0
22
0
1
Order By: Relevance
“…O efeito Marangoni é, atualmente, o mecanismo mais citado para explicar o aumento de penetração observado na soldagem A-TIG com fluxos que contém óxidos em aços inoxidáveis austeníticos, por exemplo, nas referências [24,25,27,29,31,40,44]. A sua ocorrência foi demonstrada através da filmagem do movimento de partículas na superfície da poça ou no interior desta por videoradiografia [27,44], pela determinação da evolução do teor de oxigênio na solda e da evolução do formato do cordão com a composição e densidade do fluxo [24.25,45], figuras 10 e 11, e por modelagem numérica do processo [47,50].…”
Section: Soldagem Tig Com Fluxo Ativo (A-tig)unclassified
“…O efeito Marangoni é, atualmente, o mecanismo mais citado para explicar o aumento de penetração observado na soldagem A-TIG com fluxos que contém óxidos em aços inoxidáveis austeníticos, por exemplo, nas referências [24,25,27,29,31,40,44]. A sua ocorrência foi demonstrada através da filmagem do movimento de partículas na superfície da poça ou no interior desta por videoradiografia [27,44], pela determinação da evolução do teor de oxigênio na solda e da evolução do formato do cordão com a composição e densidade do fluxo [24.25,45], figuras 10 e 11, e por modelagem numérica do processo [47,50].…”
Section: Soldagem Tig Com Fluxo Ativo (A-tig)unclassified
“…This theory was proposed by Heiple and Roper [13,14,15]. During welding, active flux is dissociated into positive ions and negative ions.…”
Section: ''""mentioning
confidence: 99%
“…The excess amount of the activating ux of B 2 O 3 or SiO 2 can cause the decrease of the penetration depth due to the decrease of the temperature coefficient of surface tension and the ow associated with the Marangoni convection. Lu 11 and Leconte et al 4,5 studied the oxygen content in the weld pool with oxide uxes, and found the dependence of the oxygen content on the melting point and the coating density of the oxide uxes. The oxygen content in the weld pool increases with the coating density of the oxide uxes to a certain extent, and the largest oxygen content is correlated with the melting point.…”
Section: Effect Of Coating Densitymentioning
confidence: 99%
“…In comparison with the activating uxes of uorides and chlorides, oxides have low toxicity and can signicantly increase the penetration depth. [3][4][5] It has been believed that the increase in the penetration depth is due to the role of oxides in controlling the arc constriction and Marangoni convection.…”
Section: Introductionmentioning
confidence: 99%